Typification of Lophopogon tridentatus, an Indian endemic (Poaceae, Andropogoneae) - Karthigeyan, Kaliyamurthy; Murugan, Perumal (Phytotaxa, 2018)
The genus Lophopogon Hackel (1887: 26) is endemic to India (Singh et al. 2015) and is represented by two species, viz. L. kingii Hook. f. (1896: 149) and L. tridentatus (Roxburgh) Hackel (1889: 254). The distribution of L. kingii is restricted to Bihar and Odisha (Chandramohan et al. 2016; Tiwari et al. 2017), whereas L. tridentatus is more widespread, distributed in Andhra Pradesh, Bihar, Gujarat, Karnataka, Madhya Pradesh, Maharashtra and Tamil Nadu. (Bor 1960; Singh & Deshpande 1980; Sur 2004; Kabeer et al. 2009). On critical study and survey of literature, it was found that the name L. tridentatus needs to be typified.